Krytyk – renegat. O Wacławie Jabłonowskim - Strzyżewski, Mirosław (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article presents Wacław Jabłonowski (c. 1810–1870), an émigré publicist and literary critic who published one of the first reviews of Juliusz Słowacki’s Beniowski, included in “Trzeci Maj” (The third of May) in 1841. Liberally using the notion of nationality as an axiom, he demonstrated the superiority of Słowacki’s long poem over Mickiewicz’s epic poem Pan Tadeusz. Jabłonowski’s writings on literature (consisting of nine articles) constitute an example of amateur manipulation, dilettantism and arbitrariness of opinion devoid of aesthetic grounds. They are, in fact, the background of Jabłonowski’s Pan-Slavic views which the community of Polish migrants living in Paris after the November Uprising unequivocally deemed to be in line with the ideas of the Russian Empire. The community considered him an apostate and a Russian spy, indicating his unclear financial activity and cases of fraud which forced him to go into hiding and escape from France, first to Algier and then to Galicia, in order to seek his brother’s protection. Relatively few archive sources concerning Jabłonowski’s life survive to this day, hence his biography suffers from numerous gaps and uncertainties.